Steel City Angels: process leads creation - Woelfel, Margaret Johanna, author; Morales, Juan J., advisor; Taylor, Ted, committee member; Arnegard, Iver, committee member (Colorado State University. Libraries, 2012)
Steel City Angels is a novel in stories that follows several flawed characters through interwoven tales centered in and around Pueblo, Colorado. The manuscript is divided into three sections: Summer, Fall/Winter and Spring to highlight not only the chronological order of the stories, but also to emphasize the unique position Pueblo occupies in regard to extreme weather as it exists in Southern Colorado's "Banana Belt". The text is written in traditional prose style, although in addition to three major story arcs across several of the stories, there are also two instances of flash fiction within the volume. Underpinned by a theoretical nod to process and post-process theory, the work contained in this manuscript was modeled after process theory hallmarks emphasizing recursive writing with an eye toward post-process considerations of economic, social, geographic, cultural and other concerns as they affect the communities within Pueblo and its surrounding environment. Other novel themes include a focus on the human condition with particular emphasis on individual isolation within and without the community, the desire to build personal identity, hope, longing - particularly for human connection - and the sometimes absurd results of efforts to bond with others are explored throughout the manuscript in an attempt to illuminate the commonalities individuals share.